The logic of adaptive sequential experimentation in policy design - Xing, Haipeng; Zhang, Xiaobo (International Food Policy Research Institute, 2013)
In this paper, we argue that economists can learn a great deal from the design principles implemented in medical research. We develop a theoretical model to show the logic of adaptive sequential experiment design in the presence of uncertainty over negative effects and discuss how to choose samples in a population to minimize the experiment cost. We also point out the applications of our proposed framework in the economic domain, such as economic reforms and new product design.